Pengaruh Perputaran Kas, Perputaran Modal Kerja, Rasio Utang, dan Ukuran Perusahaan terhadap Likuiditas pada Perusahaan Sub Sektor Logam dan Sejenisnya yang Terdaftar di Bursa Efek Indonesia - Winda Apriliyani; Hetty Muniroh (Jurnal Ilmiah Aset, 2021)
The purpose of this research was to analysis the effect of cash turnover, working capital turnover, debt ratio and firm size on liquidity. The research sample was 7 companies with 35 observations. The data analysis technique used was multiple linear regression analysis. The results of the study showed that cash turnover has an insignificant negative effect on liquidity, working capital turnover has a significant negative effect on liquidity, debt to equity ratio have a significant negative effect on liquidity and the size of the company has a significant positive effect on liquidity.